PENGARUH LINGKUNGAN KERJA FISIK DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT EL PROFESOR STEAK HOUSE CIPETE JAKARTA SELATAN - Eka Yuliana; Bambang Purnomo Yanuarso (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of work discipline and work environment on employee performance at PT El Profesor Steak House Cipete, South Jakarta, both partially and simultaneously. The sample used was a saturated sample technique totaling 56 employees. Data collection techniques through primary data and secondary data. Data analysis techniques used descriptive statistics, validity tests, reliability tests, normality tests, multicollinearity tests, autocorrelation tests, heteroscedasticity tests, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, t test and f test. The results of the analysis showed that: (1) partially there is a positive and significant influence between the physical work environment on employee performance at PT El Profesor Steak House Cipete, South Jakarta as evidenced by the simple linear regression equation Y = 24.128 + 0.422X1 and the calculated t value of 4.777> t table 2.005 from a significant value of 0.000 <0.05. (2) Partially there is a positive and significant influence between work discipline on employee performance at PT El Profesor Steak House Cipete, South Jakarta as evidenced by the simple linear regression equation Y = 26.603 + 0.368X2 and the calculated t value of 4.933 > t table 2.005 from a significant value of 0.000 < 0.05. (3) Simultaneously there is a positive and significant influence between the physical work environment and work discipline on employee performance at PT El Profesor Steak House Cipete, South Jakarta as evidenced by the simple linear regression equation Y = 22.276 + 0.240 X1 + 0.230 X2 and the calculated F value of 15.114 > F table 2.780 from a significant value of 0.000 < 0.05.